Preparation of indigenous duck (Anas platyrhynchos) skeleton to enhance veterinary anatomy teaching - Hasan, Imam; Islam, Mohammad Rafiqul (Asian Journal of Medical and Biological Research, 2019)
The objective of this study was to prepare the skeletons of duck to enhance veterinary anatomy teaching. Five aged ducks were used in this experiment, which was collected from the Bangladesh Agricultural University poultry farm. The ducks were skinned and different segments of the body were dissected with the help of a scalpel. Then the bones were wrapped using merkin clothes, heated in 5% solution of soda water for 1 hour, and kept in that solution for 7 days for decomposing the muscles, tendon and ligaments. For proper cleaning, the bones were dipped into 10% bleaching water for 2 hours. After complete sundry, the bones were articulated using super glue for rising into a skeleton. The vertebral column was aligned with 25-gauge steel wire was inserted into the vertebral foramen. Finally, the skeletons were fixed on a wooden stand. Therefore, the skeletons were preserved and used for demonstration of osteology, and avian anatomy. This duck skeleton will be used to study avian morphology and make a comparative analysis with other mammals. Asian J. Med. Biol. Res. June 2019, 5(3): 192-196